Challenge-obstacle stressors and cyberloafing among higher vocational education students: the moderating role of smartphone addiction and Maladaptive - Lizarte Simón, Emilio Jesús; Khaled Gijón, Meriem; Galván Malagón, María Carmen; Gijón Puerta, José (Frontiers in Psychology, 2024)
The start of higher vocational education and training is a new stage for students with a challenge between theoretical classes and the new expectations and demands of companies during the internship period. To understand some of the implications of stress on cyberloafing, we can distinguish between stress perceived as an obstacle that can be overcome – challenge stress – or as a threat that can block work performance – obstacle stress – and stress perceived as an obstacle that can be overcome – challenge stress – or as a threat that can block work performance – obstacle stress-. The aim of this research is to find out the relationships between challenge-obstacle stress in Cyberloafing, as well as the moderating effect of Smartphone Addiction and Maladaptive. In this study, the Challenge-Hindrance Stressors, Smartphone addiction scale-short version (SAS-SV) instrument, the Maladaptive subscale of the Cognitive Emotional Regulation Questionnaire (CERQ) and Cyberloafing were applied to 403 upper-level vocational training students from different secondary schools in all provinces of the autonomous community of Andalusia, Spain, distributed throughout the provinces that make up this autonomous community. The findings show that students’ challenge stressors do not increase Cyberloafing, enabling them to cope with the academic demands and work challenges during the theory and internship period. On the contrary, obstacle stressors generate stressful situations that undermine the acquisition of objectives and development of academic competences. In our research we observe that challenge-obstacle stressors have a disparate influence on cyberloafing. Challenge stressors are negatively related to Maladaptive. The same is not true for obstacle stressors.